2002
DOI: 10.4067/s0717-77122002000100008
|View full text |Cite
|
Sign up to set email alerts
|

Eficácia do piretróide sintético alfametrina no controle de Rhipicephalus sanguineus em cães

Abstract: The objective of this study was to evaluate the efficacy of the synthetic pyrethroid alphamethrin in the control of Rhipicephalus sanguineus in dogs. In vitro tests with filter paper was done to nonengorged larvae, engorged larvae, nonengorged nymphs, engorged nymphs and nonengorged adults of R. sanguineus, given respectively a LC 50 of 3,63;4,79;5,87;10,01 and 11,19 ppm and a LC 90 respectively of 13,17; 17,65; 29,37; 37,32 and 42,99 ppm. Different concentrations of alphamethrin was used in engorged females… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…Bittencourt (1987) evaluated the efficacy of some synthetic pyrethroids on different stages of Amblyomma cajennense and concluded that adults were more resistant than the immature ones. It was also observed by Sant'anna et al (2002), who reported that R. sanguineus adults were more resistant to different concentrations of alphamethrin, comparing to larvae and nymphs. In relation to vegetable origin products, Ribeiro et al (2008) evaluated the acaricide effect of hexane extract of Calea serrata and attested that B. microplus larvae are more susceptible than engorged females.…”
Section: Discussionsupporting
confidence: 62%
“…Bittencourt (1987) evaluated the efficacy of some synthetic pyrethroids on different stages of Amblyomma cajennense and concluded that adults were more resistant than the immature ones. It was also observed by Sant'anna et al (2002), who reported that R. sanguineus adults were more resistant to different concentrations of alphamethrin, comparing to larvae and nymphs. In relation to vegetable origin products, Ribeiro et al (2008) evaluated the acaricide effect of hexane extract of Calea serrata and attested that B. microplus larvae are more susceptible than engorged females.…”
Section: Discussionsupporting
confidence: 62%